2017
DOI: 10.5897/ajar2017.12498
|View full text |Cite
|
Sign up to set email alerts
|

Screening of guar accessions [Cyamopsis tetragonoloba (L.) Taub.] for higher yield potential under irrigated conditions

Abstract: Twelve quantitative traits such as germination percentage, days to 50% flowering, plant height, branches plant -1 , clusters plant -1 , pod length, days to maturity, 1000-seed weight and grain yield plot -1 were studied to determinate ample variation and association between 100 Guar [Cyamopsis tetragonoloba (L.) Taub , seeds pod -1 and pod length. However, branches plant -1 and days to maturity were significant but negatively correlated with grain yield plot -1 . Principal component analysis indicated the quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Seed weight adjustment as a response to water deficit is a compensatory mechanism that has not been fully explored in guar. Majority of related reports indicate number of pods per plant as a yield component that is typically affected by water stress in guar (Avola et al., 2020; Khalid et al., 2017; Stafford & McMichael, 1991). To our knowledge, this study is the first to report on the observed tradeoff between pod production and seed weight for guar under water‐limited conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Seed weight adjustment as a response to water deficit is a compensatory mechanism that has not been fully explored in guar. Majority of related reports indicate number of pods per plant as a yield component that is typically affected by water stress in guar (Avola et al., 2020; Khalid et al., 2017; Stafford & McMichael, 1991). To our knowledge, this study is the first to report on the observed tradeoff between pod production and seed weight for guar under water‐limited conditions.…”
Section: Resultsmentioning
confidence: 99%